38.4k views
5 votes
Simplify the expression.

Simplify the expression.-example-1
User Yelena
by
5.0k points

2 Answers

4 votes

Answer:

Choice b is the answer.

Explanation:

We have given an expression.


(secx)/(tanx)

We have to simplify given expression.

Since, we know that

secx is reciprocal of cosx.


secx=(1)/(cosx)

tanx is ratio of sinx to cosx.


tanx=(sinx)/(cosx)

Putting above formulas in given expression ,we have


(1)/(cosx) ÷
(sinx)/(cosx)


(1)/(cosx) ×
(cosx)/(sinx)


(1)/(sinx)

Hence, cscx is reciprocal of sinx.


(secx)/(tanx) = cscx

User RickL
by
5.2k points
2 votes

Answer:

The answer is (b) cscx

Explanation:

∵ secx = 1/cosx

∵ tanx = sinx/cosx

∴ secx/tanx = 1/cosx ÷ sinx/cosx

= 1/cosx × cosx/sinx

= cscx

User Nicola Musatti
by
4.9k points